Super Early Pigeonpea- Scope and Opportunities in India - Kumar, M. Parimala; Devi, K. B. Suneetha; Naik, B. Balaji; Jayasree, G.; Sreekanth, P. D.; Kumar, C. V. Sameer (Chronicle of Bioresource Management, 2023)
Pigeonpea is a one of the oldest food crops to provide rich source of food proteins. It occupies an important place among pulses and has been rated the best as far as its biological value is concerned. It has been recommended for a balanced diet with cereals, especially to fill in the nutritional gap for proteins among the poorer section in developing economies that cannot afford a non-vegetarian diet. The available medium and long duration pigeonpea cultivars grown under rainfed conditions were experiencing terminal drought at flowering due to cessation of the south west monsoon in October leading to lower productivity in India. The photo and thermo sensitivity of existing pigeonpea cultivars is also another drawback restricting the horizontal expansion to different cropping systems in varied agro-ecologies. The scope of yield maximization in pigeonpea could be possible through cultivation of photo and thermo in-sensitive super early pigeonpea types.